2003
DOI: 10.1007/s00464-002-9246-3
|View full text |Cite
|
Sign up to set email alerts
|

Earlier appearance and higher incidence of the rectoanal relaxation reflex in patients with imperforate anus repaired with laparoscopically assisted anorectoplasty

Abstract: In the early postoperative stage, patients repaired with LAR had more favorable findings in anorectal manometry than patients repaired with PSARP. Long-term follow-up studies to confirm a superior defecation continence achieved with LAR are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 11 publications
2
60
1
1
Order By: Relevance
“…For evaluation of the state of continence in this study, we mainly relied upon the number of motions per day and the presence of soiling in between motion as described by Lin et al (13) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For evaluation of the state of continence in this study, we mainly relied upon the number of motions per day and the presence of soiling in between motion as described by Lin et al (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the technique of LAARP the number of series in the literature is still small to draw statistical significance. However, Lin et al (13) used the number of motions per day for the early clinical assessment of nine cases of high imperforate anus after LAARP. Seven of nine LAARP patients had an acceptable frequency of one to four bowel openings per day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our twenty eight patients, 6 patients (21.4%) developed constipation, all these cases responded well for the conservative treatment using laxatives and bowel habit training programs. For evaluation of the state of continence in this study, we mainly relied upon the number of motions per day and the presence of soiling in between motion as described by Lin et al (13) . The overall result of our study as regard continence showed that 50% had good, 36% moderate and 14% poor results.…”
Section: Discussionmentioning
confidence: 99%
“…Upon analysis of the diagnostic methods available for the assessment of the anorectal region, manometry is one among the most important tools for the identification of sphincter defects and the elucidation of fecal incontinence [12][13][14][15][16] and intestinal constipation [17][18][19]. On the other hand, sphincter trauma does not occur on a regular basis, making the grouping of patients by lesion type difficult, not to mention the fact that understanding of the lesion anatomy and physiopathology is rather poor.…”
Section: Introductionmentioning
confidence: 99%